REPORT OF THE WASC VISITING TEAM EDUCATIONAL EFFECTIVENESS REVIEW
The commitment to the mission of CSUCI, a truly "lived mission," greatly impressed teams from the Western Association of Schools and Colleges. During the Capacity and Preparatory Review, a team visited CSUCI March 6-8, 2006. During the visit, team members met with faculty, administrators, students, and staff who discussed the self-study report and the campus' ability to fulfill its core commitments to capacity. A second visit took place March 14 — 16, 2007, for an Educational Effectiveness Review, which is the focus of this report. Team members met with faculty, staff, students, and administrators who discussed CSUCI's ability to meet institutional and programmatic objectives and how review processes, including data collection and reflection of evidence, are used to enhance educational effectiveness.